Birth weight and hospital admission before the age of 2 years. Issue 7 (July 1992) - Mutch, L; Ashurst, H; Macfarlane, A
Abstract : Admission rates to hospital of children born weighing 1500 g or less were compared with those born with birth weights over 1500 g in a retrospective analysis of routinely collected data from the Oxford Record Linkage Study. The children were born in the three five year periods 1968-72, 1974-8, and 1979-83 to women resident in Oxfordshire and West Berkshire. The main measures of the study were survival rates to 28 days after birth and hospital admissions of survivors up to the age of two years. Among babies weighing 1500 g or less, neonatal survival rates rose from 350.2 per 1000 total births in 1968-72 to 577.4 per 1000 among births in 1979-83. Over the same period, the proportion of children admitted to hospital at least once before the age of 2 years rose from 218.6 per 1000 survivors to 444.4 per 1000. In the children with birth weights over 1500 g, survival rates rose from 985.5 to 995.9 per 1000 births and hospital admission rates rose from 98.2 to 144.4 per 1000 survivors over the same time period. Although very low birthweight children did not contribute significantly to total hospital bed occupancy, because their numbers were small in relation to the total number of children in the population, their contribution increased between the five year periods 1968-72 and 1979-83. It should therefore be continuously monitored using routine systems.